2019
DOI: 10.1007/s13197-019-03635-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of electrochemical biosensor based on CNT–Fe3O4 nanocomposite to determine formaldehyde adulteration in orange juice

Abstract: An electrochemical biosensor was developed to determine formaldehyde (HCHO) adulteration commonly found in food. The current responses of various electrodes based on multiwalled carbon nanotubes (CNTs) and synthesized nanocomposite (CNT-Fe 3 O 4) were measured using cyclic voltammetry. The nanocomposite based biosensor shows comparatively high sensitivity (527 lA mg/L-1 cm-2), low detection limit (0.05 mg/L) in linear detection range 0.05-0.5 mg/L for formaldehyde detection using formaldehyde dehydrogenase (FD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The studies demonstrated the capability of the voltammetry technique to perform a quick representation of urea-corrupted milk segregation and nectar test. (Kundu et al 2019 ).…”
Section: Assessment Methods Using Odour and Tasting Sensing Technologymentioning
confidence: 99%
“…The studies demonstrated the capability of the voltammetry technique to perform a quick representation of urea-corrupted milk segregation and nectar test. (Kundu et al 2019 ).…”
Section: Assessment Methods Using Odour and Tasting Sensing Technologymentioning
confidence: 99%
“…Synthesis of magnetic amine-functionalized carbon nanotubes (NH 2 -CNTs/Fe 3 O 4 ). NH 2 -CNTs/Fe 3 O 4 was synthesized by the chemical coprecipitation method 30 as follows:…”
Section: Methodsmentioning
confidence: 99%
“…However, these methods are highly sophisticated, expensive, time-consuming and require large amount of samples. 2,8,9 To overcome these limitations, we require a more rapid, authentic, simple, and cost-effective technique for AFB1 detection. In this context, electrochemical nanobiosensors for food toxin detection have triggered high research interest owing to their excellent sensitivity, simplicity, high signal power to noise power ratio, and short output time.…”
Section: Introductionmentioning
confidence: 99%